Carbon substrates utilization determine antagonistic fungal-fungal interactions among root-associated fungi - Kemmerling, Rosa; Dintilhac, Louise-Elisabeth; Zancarini, Anouk; Mataigne, Alice; Mougel, Christophe; Vannier, Nathan (Frontiers in Microbiology, 2025)
IntroductionThe assembly of the plant microbiome results from a complex network of interactions. The role of microbial taxa in shaping the microbiome has recently gained attention, emphasizing the competitive dynamics and chemical warfare occurring within this dynamic environment. Within and around the roots, microbe-microbe interactions are piloted by nutritional constraints that can be modulated by the host. In this context, while nutrient blocking and antimicrobial production have largely been described as competitive traits in bacterial taxa, the importance of fungal metabolism in determining fungal-fungal interactions remains largely unexplored.MethodsIn this work, we profiled the carbon substrate utilization of 91 root-associated fungal isolates from Brassica napus and Triticum aestivum and evaluated their antagonistic abilities against two agronomically relevant fungal competitors, Rhizoctonia solani and Fusarium graminearum.ResultsOur results indicate that fungi arbor contrasted carbon utilization profiles and strategies that are independent from the two host plant species tested, the plant compartment and the geographic region. Strikingly, specific carbon utilization signatures were associated with antagonistic abilities with antifungal-mediated antagonism characterized by higher utilization rates of diverse carbon substrates while direct competitive abilities were associated with lower utilization rates of fewer carbon substrates.DiscussionTogether with taxonomy-based predictions of antagonism-specific enzymatic reactions, these results suggest that carbon utilization profiles and enzymatic reactions prediction could be considered as markers of fungal antagonistic potential. From an ecological point of view, our results suggest that root-associated fungi have contrasted carbon usage strategies likely shaped by and determining fungal-fungal antagonistic interactions.